Mitochondrial alternative oxidase is involved in both compatible and incompatible host-virus combinations in Nicotiana benthamiana - Zhu, Feng; Deng, Xing-Guang; Xu, Fei; Jian, Wei; Peng, Xing-Ji; Zhu, Tong; Xi, De-Hui; Lin, Hong-Hui (Plant science (Limerick), 2015)
•We studied the mechanisms of AOX in the systemic antiviral defense response.•We used VIGS to investigate the role of AOX in N-mediated resistance to TMV.•NbAOX plays an important role in the systemic resistance to virus infection.•NbAOX is required for N-mediated resistance to TMV. The alternative oxidase (AOX) functions in the resistance to biotic stress. However, the mechanisms of AOX in the systemic antiviral defense response and N (a typical resistance gene)-mediated resistance to Tobacco mosaic virus (TMV) are elusive. A chemical approach was undertaken to investigate the role of NbAOX in the systemic resistance to RNA viruses. Furthermore, we used a virus-induced gene-silencing (VIGS)-based genetics approach to investigate the function of AOX in the N-mediated resistance to TMV. The inoculation of virus significantly increased the NbAOX transcript and protein levels and the cyanide-resistant respiration in the upper un-inoculated leaves. Pretreatment with potassium cyanide greatly increased the plant's systemic resistance, whereas the application of salicylhydroxamic acid significantly compromised the plant's systemic resistance. Additionally, in NbAOX1a-silenced N-transgenic Nicotiana benthamiana plants, the inoculated leaf collapsed and the movement of TMV into the systemic tissue eventually led to the spreading of HR-PCD and the death of the whole plant. The hypersensitive response marker gene HIN1 was significantly increased in the NbAOX1a-silenced plants. Significant amounts of TMV-CP mRNA and protein were detected in the NbAOX1a-silenced plants but not in the control plants. Overall, evidence is provided that AOX plays important roles in both compatible and incompatible plant-virus combinations.